DYNAMICS OF SOME PHYSICAL AND CHEMICAL PROPERTIES OF SALIVA IN SURGICAL TREATMENT OF LIVER ALVEOCOCCOSIS - A. K. Martusevich; O. B. Zhdanova; V. A. Yanchenko (Российский паразитологический журнал, 2016)
Dynamics of crystallogenic and initiating properties of saliva in patients with alveococcosis during the surgery and in the late postoperative period were specified. Saliva samples of 22 patients with liver alveococcosis were examined at the Kirov Zonal Hepathology Center. The diagnosis has been verified by instrumental methods (ultrasound examination, computer and/or magnetic-resonance tomography) and laboratory tests (latex agglutination test and enzyme-linked immunosorbent assay). A successful surgical treatment has been conducted in all patients. Crystal-logenic properties of saliva were estimated by the methods of crystalloscopy and thesigraphy along with a criteria-based definition of facies. A spectrometric examination of crystalloscopic and thesigraphic facies of saliva has also been conducted. It was determined that the surgical treatment of liver alveococcosis leads to a partial normalization of the crystallogenic and initiating properties of saliva already on checking out from hospital.